The Effect of a Theory of Planned Behavior-based Educational Intervention on Sexual and Reproductive Health in Iranian Adolescent Girls: A Randomized Controlled Trial - Darabi, Fatemeh; Yaseri, Mehdi; Kaveh, Mohammad Hossein; Khalajabadi Farahani, Farideh; Majlessi, Fereshteh; Shojaeizadeh, Davoud (Journal of research in health sciences, 2017)
We aimed to assess the effect of a theory of planned behavior (TPB)-based educational intervention on attitude, norms, parental control, behavioral control, and intention in high school girls in Tehran, Iran. Randomized controlled trial. This study was conducted among 578 high school girls, 12 to 16 yr, in Tehran, Iran in 2016. The subjects were randomly assigned to the experimental (n=289) and control (n=289) groups using multistage random cluster sampling. TPB is the basis for both education and evaluation; therefore, the TPB-based questionnaire was used before and after the intervention. The intervention included three months education and six months follow up. The obtained data were analyzed using SPSS version 16 through statistical tests and analysis of covariance. Significant improvement in attitude (difference=16.8; 95% CI: 15.3, 18.3), subjective norms (16.4; 95% CI=14.83 to 18.11), perceived behavioral control (18.0; 95% CI: 16.6, 19.4), perceived parental control (17%; 95% CI: 15.1, 18.9), behavioral intention (18.4%; 95 CI: 14.8, 18.3), and behavior (18.5; 95% CI:16.8, 20.2) was observed in experimental group compared to control group (P<0.001). Theory-based educational intervention in sexual and reproductive health can effectively reduce the high-risk behaviors related to sexual and reproductive health in adolescent girls. Health and education policy-makers are advised to review the current education programs and replace them with new influential education programs related to sexual and reproductive health in the school system.